2013
DOI: 10.2340/00015555-1445
|View full text |Cite
|
Sign up to set email alerts
|

Effective Control of Recalcitrant Pruritus by Bevacizumab: A Possible Role for Vascular Endothelial Growth Factor in Chronic Itch?

Abstract: Prurigo is a difficult to treat condition characterized by severe pruritus presenting with chronic secondary scratch lesions. We report here a dramatic improvement in pruritus in a patient with prurigo simplex who was being treated with bevacizumab, a monoclonal vascular endothelial growth factor (VEGF) antibody. On the basis of the increased VEGF expression measured in the skin of this patient, serum levels of VEGF were subsequently analysed in 27 consecutive patients with prurigo and 19 healthy controls. VEG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 17 publications
(21 reference statements)
2
18
0
Order By: Relevance
“…In patients with atopic dermatitis (AD), VEGF‐A expression levels in the stratum corneum correlate with the scores of itch . Serum VEGF‐A levels are increased in patients with prurigo and correlate with disease activity . Based on our results and previous reports, VEGF‐A expression can be a marker for pruritus in several skin diseases.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In patients with atopic dermatitis (AD), VEGF‐A expression levels in the stratum corneum correlate with the scores of itch . Serum VEGF‐A levels are increased in patients with prurigo and correlate with disease activity . Based on our results and previous reports, VEGF‐A expression can be a marker for pruritus in several skin diseases.…”
Section: Discussionsupporting
confidence: 77%
“…A VEGF‐A inhibitor, bevacizumab, is used for the treatment of several malignancies through suppression of angiogenesis. In addition, there is an anecdotal report of a patient with prurigo whose pruritus improved after receiving bevacizumab . Furthermore, axitinib, a selective inhibitor of VEGFR tyrosine kinases 1–3, suppressed the scratching behavior in an imiquimod‐induced psoriasiform dermatitis mouse model .…”
Section: Discussionmentioning
confidence: 99%
“…Our data and hints from the literature together point towards VEGF as a promising pharmacological target in prurigo. Recently, we reported the complete control of chronic pruritus in a patient with prurigo with bevacizumab, a monoclonal anti‐VEGF antibody . Bevacizumab and other VEGF or VEGF receptor blockers are currently used in anti‐tumour therapy and should be evaluated for their anti‐inflammatory potential.…”
Section: Discussionmentioning
confidence: 99%
“…As antihistamines are not sufficient to suppress pruritus in most prurigo patients, immunosuppressive therapies such as cyclosporine and various off‐label therapies have been used, with variable success . Recently, we reported that pruritus in a prurigo patient was dramatically improved after treatment with the VEGF antagonist Bevacizumab for breast cancer . This observation led us to hypothesize that VEGF‐A may be involved in the pathogenesis of prurigo.…”
Section: Introductionmentioning
confidence: 99%
“…32 In mice, IL-31 induces pruritus through IL-31 receptors that are expressed by the primary afferent neurons, mediating action through the TRPV1 and TRPA1 ion channels. 34,35 IL-31 also promotes β-endorphin production by keratinocytes to transmit itch sensation. 33 It has been proposed that IL-31 induces pruritus indirectly via keratinocytes and subsequently released secondary mediators such as vascular endothelial growth factor (VEGF).…”
Section: Immune Mechanisms Of Pruritus In Admentioning
confidence: 99%